LITHO STABILIZATION OF THE LATERITIC GRAVELLY BY GRANITE CRUSHED FOR THEIR USE IN FLEXIBLE PAVEMENT IN BENIN - Babaliye, Olivier; HOUANOU, KOCOUVI AGAPI; VIANOU, COKOU ANTOINE; TCHEHOUALI, DÈFODJI ADOLPHE; FOUDJET, Erick Amos (My University, 2020)
This study shows the improvement of laterite from Benin whose borrowing is abandoned with class 0/31.5 granite crushed stone for its use in road construction according to the rules of CEBTP of 1972, revised in 1984. The validation of this method called litho stabilization was carried out by determining the cohesion and the internal friction angle. The results of the mixes 35% crushed + 65% laterite and 40% crushed + 65% laterite meet the criteria of CEBTP, 1984 for the foundation layer of flexible pavements. We carried out the direct shear test on natural laterite and the two mixtures used as a foundation layer for flexible pavements in order to identify the best mix. On the one hand the 35% crushed mixture plus 65% laterite gave: 26.46 KPa of cohesion and 30.30 of internal friction angle at 100% OPM, on the other hand the 40% crushed mixture plus 60% laterite gave: 4.75 Cohesion KPa and 27.420 internal friction angle at 100% OPM. All these properties are superior to that of natural laterite except the cohesion of the 40% crushed mixture. This confirms that the addition of crushed stone makes the laterite rigid and dense.
Keywords: Laterite; Improvement; Geotech; Road; Construction; Granite Crushed